Predicting TUrnover Intentions of Hotel Employees: The Influence of Employee Development Human Resource Management Practices and Trust in Organization - Mohamad Abdullah Hemdi; Aizzat Mohd. Nasurdin (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2006)
This study investigates the variables that may be predictive of hotel employees’ turnover intentions. The influence of trust in organization as a mediator in the proposed relationship is also examined. A total of 380 operational employees from 5-star rated hotels completed the questionnaires. Hierarchical regression analysis was used to test the relationships hypothesized in the model. Most of the hypotheses were supported. It is suggested that to enhance employees’ trust in organization and subsequently to reduce turnover intentions, hotels need to continue to provide training and development programs to their employees, conduct fair and formal appraisal system, and provide ample and clear career advancement to their employees. Limitations and suggestions for future studies are forwarded.